Axially symmetric magnetic mirror traps. Recent progress in plasma confinement and heating - Kruglyakov, E.P.; Burdakov, A.V.; Ivanov, A.A. (Вопросы атомной науки и техники, 2009)
New results of studies of plasma heating and confinement in the axisymmetric mirror traps are presented. It is shown that due to excitation of the instability at the bounce frequency (bounce instability) the effects of multi-mirror confinement can observed even at the densities by two-three-orders of magnitude lower than those predicted by the Budker, Mirnov and Ryutov theory (GOL-3 facility). This effect makes the multi-mirror reactor more realistic. A small size mirror cell was incorporated with the gas dynamic trap (GDT). Due to the transverse injection of two neutral beams (ENB=20 keV) ion hot plasma was obtained in the compact mirror cell. As a result of that the plasma flux to the end wall decreased by 5 times. Besides, the threshold of the Alfven ion cyclotron instability (AIC) was determined in the same experiment with accumulation of fast ions in the compact cell. It follows from this experiment that in the GDT based neutron source the AIC instability will not excite in spite of anisotropic plasma.